An Age of Exalted Harmony? Deciphering the Contested Historiography of the Jingtai Reign. (2nd January 2021) - Throness, Aaron
Abstract : The contested historiography of the Jingtai Emperor remains a largely untouched subject in contemporary Ming scholarship. In an attempt to contribute to this field of study, this essay surveys and analyses the works of his detractors and supporters both in the immediate aftermath of his reign and beyond, while simultaneously tracing the process whereby the Jingtai reign was first disparaged and then gradually rehabilitated. It contends that the patterns discernible in how Ming writers thought about the Jingtai reign reveal a schism between ritual-oriented detractors and function-oriented supporters, both of whom were locked in a historiographical deadlock concerning standards of imperial rulership during an unprecedented crisis. It further argues that a confluence of trends including the vibrant intellectual activity of post-Tumu Ming China, the compilation of private histories incongruent with official ones, and dissatisfaction with official historiography contributed to the salvaging of Zhu Qiyu's unconventional reign.